MENJUAL BERAS TIDAK SESUAI DENGAN HARGA PENETAPAN PEMERINTAH MENURUT IBNU TAIMIYAH (Studi Kasus di Pasar Sumbul Kelurahan Pegagan Julu I Kecamatan Sumbul Kabupaten Dairi) - Ganda Hidayah Simbolon (ISLAMIC BUSSINESS LAW REVIEW, 2019)
Rice is one of the main and primary commodities for the community, to be able to meet those needs, there should be no cheating and high prices so that people can meet their needs. In Sumbul Market, the price of rice is quite high, and varies, there is no specific benchmark. Each seller is free to determine the price of rice in the market. The results showed, the concept of determining the price of basic commodities according to Ibn Taymiyyah was mandatory, with the condition that the price increase that occurred in the market was due to fraud from the hoarder, for example, but it was unlawful if the increase was based on normal conditions which should be a trading process in the market. Determination of the price of rice that occurs in the Sumbul Market Pegagan Julu I Village Sumbul Dairi Regency is set freely by the seller, and there is no fixed price, each seller has a different price. The law of selling rice is not in accordance with the price set by the government according to Ibn Taymiyyah is forbidden, if there is defiance, the government is obliged to force sellers to sell their merchandise at market prices / qimah al-mitsil, if it is ignored, the seller is not allowed to sell on the market.